2011
DOI: 10.1097/gme.0b013e3181e750dd
|View full text |Cite
|
Sign up to set email alerts
|

Oral postmenopausal hormone therapy, C-reactive protein, and cardiovascular outcomes

Abstract: Objectives-This study examines C-reactive protein (CRP) levels predict cardiovascular events (CVE) among hormone therapy (HT) users and non-users.Background-CRP levels are higher in women who use oral HT than in non-users; however, whether the same CRP cutpoints determine increased cardiovascular risk remains unanswered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…37 In a subanalysis of the Women's Health Study, Kurtz et al 38 showed that CRP had a linear relationship in predicting cardiovascular events among both HT users and nonusers; in particular, CRP levels of 3 mg/L or higher were associated with increased cardiovascular risk in both HT users and nonusers. A prospective study of healthy postmenopausal women concluded that baseline CRP concentration is an independent risk factor for cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 98%
“…37 In a subanalysis of the Women's Health Study, Kurtz et al 38 showed that CRP had a linear relationship in predicting cardiovascular events among both HT users and nonusers; in particular, CRP levels of 3 mg/L or higher were associated with increased cardiovascular risk in both HT users and nonusers. A prospective study of healthy postmenopausal women concluded that baseline CRP concentration is an independent risk factor for cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 98%
“…(Vongpatanasin et al, 2003;Mosca et al, 2004) Data from the WHI and the Women's Health S t u d y h a v e d e m o n s t r a t e d t h a t C R P p r e d i c t s C V D r i s k i n p o s t -m e n o p a u s a l w o m e n independent of HRT. (Kurtz et al, 2011) HRT use had less predictive value than CRP levels in these studies. Thus, the clinical significance of hormone-related changes in circulating CRP levels remains uncertain.…”
Section: Estrogen Effects On Lipoproteinsmentioning
confidence: 58%
“…13 Their findings are provocative, though. As with many studies, these results generate more questions than answers: should risk stratification for CRP differ for women taking transdermal versus oral estrogen therapy?…”
mentioning
confidence: 89%
“…8 According to the conclusions by Kurtz et al, 13 women on hormone therapy have the same CVD risk at the same CRP level as women not taking hormone therapy. However, had those women not initiated oral estrogen, would their CRP level be half of that measured, and possibly, would their CVD risk also be half?…”
mentioning
confidence: 90%
See 1 more Smart Citation